Shoreline Change Analysis of the Eastern Coast of Ghana between 1991 and 2020 - Puplampu, Dzifa Adimle; Iddris, Khiddir; Alorbu, Victor; Asante, Jonathan Otumfuor; Takaman, Judges Laar; Owusu, Alex Barimah (Journal of Environmental Geography, 2023)
The Eastern Coastline of Ghana is facing intense natural and anthropogenic disturbances, which pose a serious threat to the coastal community, ecosystem, and livelihoods. This study assessed the shoreline changes occurring along the Eastern Coast of Ghana stretching 149 km from Laloi Lagoon West of Prampram to Aflao, Ghana. The study utilizes satellite images from Landsat 4TM, Landsat 7 ETM+, and Landsat 8 OLI taken between 1991 and 2020. Data pre-processing techniques using ENVI 5.3 included calibration, layer stacking, mosaicking, and supervised classification. Post-classification shorelines were extracted using ArcGIS 10.7, and the DSAS tool was used to determine the rate of change over the 29-year period. The results showed that the coastline experienced an average erosion rate of 9 m/y and a maximum rate of 24 m/y, however, the accretion rate (3 m/y) was much lower, reflecting general coastline retreat. Thus, some 25 coastal communities are highly exposed to shoreline erosion. Sustaining the coastal area may require coastline re-engineering interventions. This study recommends continuous monitoring of the shorelines to ensure the protection of livelihoods. Implementation of both hard engineering and ecosystem-based adaptation strategies may be required to achieve holistic results toward sustainable coastal management.